Synthesis and identification of heteroaromatic N-benzyl sulfonamides as potential anticancer agents. Issue 36 (30th August 2019) - Hopkins, Megan D.; Abebe, Felagot A.; Scott, Kristina A.; Ozmer, Garett L.; Sheir, Alec A.; Schroeder, Lucas J.; Sheaff, Robert J.; Lamar, Angus A.
Abstract : The regioselective incorporation of a sulfonamide unit to a broad range of heteroarene scaffolds has been developed. Synthesized N -benzyl sulfonamides have been screened against a variety of cancer cell lines for cytotoxicity effects. Abstract : Sulfonamides are a crucial class of bioisosteres that are prevalent in a wide range of pharmaceuticals, however, the available methods for their production directly from heteroaryl aldehyde reagents remains surprisingly limited. A new approach for regioselective incorporation of a sulfonamide unit to heteroarene scaffolds has been developed and is reported within. As a result, a variety of primary benzylic N -alkylsulfonamides have been prepared via a two-step (one pot) formation from the in situ reduction of an intermediate N -sulfonyl imine under mild, practical conditions. The compounds have been screened against a variety of cell lines for cytotoxicity effects using a Cell Titer Blue assay. The cell viability investigation identifies a subset of N -benzylic sulfonamides derived from the indole scaffold to be targeted for further development into novel molecules with potential therapeutic value. The most cytotoxic of the compounds prepared, AAL-030, exhibited higher potency than other well-known anticancer agents Indisulam and ABT-751.